[OP.7A.09] A NATIONWIDE EVALUATION OF BLOOD PRESSURE CONTROL IN FRANCE USING HOME BLOOD PRESSURE MONITORING: THE FRENCH LEAGUE AGAINST HYPERTENSION SURVEY (FLAHS 2015). (September 2016) - Vaïsse, B.; Pannier, B.; Hanon, O.; Mourad, J.-J.; Girerd, X.
Abstract : Objective: In 2010, FLAHS survey indicated a 50% control in treated hypertensive patients in France. In 2015, the goal was to make a new estimate of control of hypertension in subjects aged 55 and over living in metropolitan France. Design and method: FLAHS 2015 was performed cross-sectionally on 882 subjects, part of a sample of 6 379 subjects selected as being representative of the French metropolitan population for age (55 years and above), gender, socioeconomic status, and place of living. 2 814 subjects declared taking an antihypertensive medication and detailed the name of his treatment. 1724 subjects declared taking their blood pressure at home with an electronic monitor. 882 subjects treated with antihypertensive medication monitored their BP at home (3 measures in the morning and in the evening on 3 consecutives days). The average of 12 readings over 3 days led to classify each subject as controlled by the thresholds of SBP/DBP < 135/85 or SBP < 145 in elderly over 80 years. Results: In treated hypertension, 55.4% are controlled with an average < 135/85 and 71.7% with an average < 140/90. Age, gender and weight are determinants of the performance of the BP control. Control is better among women (60.3%) than in men (50.1%), in subjects aged 55–64 (57.6%) than those aged 80 and over (49.1 %), in subjects with BMI < 25 (63%) than those with BMI > 30 (54%). When the threshold control is adapted in patients aged 80 and over to a SBP < 145 the proportion of controlled subjects came to this age group to 74.7% and control of hypertension for the entire population of elderly hypertensive patients treated and 55 years living in France is 61%. Conclusions: Control of hypertension evaluated by home blood pressure monitoring on a representative population of subjects aged 55 and over, living in France, is estimated between 50.1% and 74.7% in relation to age, gender and weight of subjects. These data indicate a mild improvement in blood pressure control in treated hypertensive patients since the FLAHS 2010 survey.